Determination of Antibacterial and Technological Properties of Vaginal Lactobacilli for Their Potential Application in Dairy Products - Siroli, Lorenzo; Patrignani, Francesca; Serrazanetti, Diana I.; Parolin, Carola; Ñahui Palomino, Rogers A.; Vitali, Beatrice; Lanciotti, Rosalba (Frontiers in Microbiology, 2017)
Functional foods could differently affect human health in relation to the gender. Recent studies have highlighted the anti-Candida and anti-Chlamydia activities of some Lactobacillus strains isolated from the vagina of healthy women. Considering these important beneficial activities on women's health, the preparation of functional food containing active vaginal lactobacilli can represent a great scientific challenge for the female gender. In this context, the aim of this work was to study some functional and technological properties of 17 vaginal strains belonging to the species Lactobacillus crispatus, Lactobacillus gasseri and Lactobacillus vaginalis in the perspective to include them in dairy products. The antagonistic activities against the pathogenic and spoilage species associated to food products and against the principal etiological agents of the genitourinary tract infections were evaluated. Moreover, the vaginal lactobacilli were characterized for their antibiotic resistance, and for their fermentation kinetics and viability during the refrigerated storage in milk. Finally, the volatile molecule profiles of the obtained fermented milks were determined. The results showed that several strains, mainly belonging to the species Lactobacillus crispatus, exhibited a significant antagonistic activity against spoilage and pathogenic microorganisms of food interest, as well as against urogenital pathogens. All the vaginal lactobacilli showed antimicrobial activity against strains belonging to the foodborne pathogenic species Listeria monocytogenes, Listeria innocua, Eenterococcus faecalis and Escherichia coli. In addition, most of the Lactobacillus strains were active towards the main pathogens responsible of vaginal and urinary tract infections including Staphylococcus aureus, Enterococcus faecium, Gardnerella vaginalis, and Proteus mirabilis. The antimicrobial activity can be attributed to the high production of organic acids. The fermentation kinetics in milk indicated the unsuitability of these lactobacilli as fermentation starters for the industrial production of dairy products. However, some strains, belonging to the species Lactobacillus crispatus and Lactobacillus gasseri, maintained a high viability in pasteurized milk at 4 °C for over a month, showing their potential application as adjunct cultures for the production of female gender foods. These data represent a first step for the set-up of a new functional dairy product, directed to the women well-being, contributing also to innovate the dairy sector.